KUALITAS UDARA DI RUANGAN RSUD NAMLEA KABUPATEN BURU PROVINSI MALUKU - Tina Amnah Ningsih; Farha Assagaff (Jurnal Ilmu dan Teknologi Kesehatan Terpadu)
Hospital air quality is one of the causes of nosocomial infections.  This study aimed to determine the relationship between the number of airborne germs and the quality of the physical environment in the air.  This type of research is analytic observational with a cross-sectional design.  The results showed that the number of airborne germs in the operating room of the Namlea Hospital did not meet the requirements based on Permenkes No. 7 of 2019.  The temperature quality in the emergency room, HCU/ICU room, and the delivery room did not meet the requirements.  The humidity and lighting in all the examined rooms also did not meet the requirements according to Permenkes no. 7 of 2019.  Based on the results of statistical tests, the Spearman correlation test showed that the temperature, humidity, and lighting of the Namlea Hospital room did not significantly correlate with the number of germs in the room air (p-value > 0.05).  The conclusion of this study showed that humidity and lighting and the number of airborne germs in the operating room at Namlea Hospital did not meet the requirements.  Based on the results of statistical tests, there is no relationship between the number of germs in the room air and the quality of the physical environment (p-value > 0.05).  This may be because the data scale uses a numerical data scale, and the results of the data normality test show that the data distribution is not expected because the sample size is small.  Suggestions for Namlea Hospital to improve the quality of the physical environment and air microbes.